Special Section on the Future University Press in Canada - Bradley-St-Cyr, Ruth (Journal of Scholarly Publishing, 2018)
The introduction and five articles that lead off the January 2018 issue compose a special section of the Journal of Scholarly Publishing (JSP). This group of papers came as a windfall to the current co-editors of JSP from a prior arrangement between Tom Radko, former editor of JSP, and Ruth Bradley-St-Cyr, guest editor of the special section. Assembling the contents of the special section was the work of Bradley-St-Cyr, who explains the provenance of and gives a context for the contents in the following introduction. The co-editors are grateful to Bradley-St-Cyr for curating these forward-facing contributions to JSP.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMzEzOC9qc3AuNDkuMi4xNDU